A Talent for Living: Exploring Ghana's 'New' Urban Childhood. (6th July 2011) - Mizen, Phil; Ofosu‐Kusi, Yaw
Abstract : This paper considers the lives of children living in a large informal settlement in central Accra, Ghana. Its contention is that children remain largely absent from the renewal of interest in slums and that where they do feature it is largely as objects of risk and vulnerability. Such an exclusive focus, it is argued, risks effacing the ways in which children are capable of actively confronting the terrible constraints posed by slum environments and the 'talent for living' that this involves. Drawing upon the findings of a small qualitative exploratory research project, the paper examines sources of support and cooperation between children and how their decisions to work are perceived as a strategy to actively support mothers and families struggling for a subsistence.